Effectiveness of cognitive behaviour therapy in improving self esteem among smart phone Addicts - a pilot study (Funded work) - MRS. GRACE LYDIA SAROJINI MOT; MS.PRIYA.G ,BOT (International Journal of Pharma and Bio Sciences, 2017)
This study aims to determine the effectiveness of CBT in improving self-esteem among smartphone addicts and to determine whether there is a correlation between the levels of self esteem and smartphone addiction. This study was conducted among college students (17-21). Pre-test and post-test assessments were obtained using Smartphone Addiction Inventory (SPAI) and Rosenberg Self Esteem Scale (RSE). A comprehensive 8 weeks CBT program was given in three-phase approach - Behaviour modification, Cognitive restructuring, Harm reduction therapy. Additionally, coping strategies were also taught to participants.Wilcoxon Signed Rank test was used to find the significant difference with p value of 0.001 result shows that there is a significant difference between pre and post-test values of the RSE score. Pearson correlation test was used to find out the correlation between levels of self-esteem and Smartphone addiction with r value of -0.488 in pre-test and - 0.958 in post-test, there exists a negative correlation between SPAI and RSE i.e., after intervention when the level of Self-esteem is increased there is a significant decrease in the level of Smartphone Addiction. Hence CBT is effective.